Effects of the Agrivoltaic System on Crop Production: The Case of Tomato (Solanum lycopersicum L.) - Aurelia Scarano; Teodoro Semeraro; Antonio Calisi; Roberta Aretano; Caterina Rotolo; Marcello S. Lenucci; Angelo Santino; Gabriella Piro; Monica De Caroli (Applied Sciences, 2024)
Climate change, with rising temperatures, water crises, and an increased frequency of climate disturbances, poses a threat to the ability of agroecosystems to ensure human access to food by affecting both the quantity and quality of crop production. Currently, there is growing knowledge about the fact that agrivoltaic systems may represent a direct strategy to cope with climate change driven by carbon dioxide emissions for energy production, preserving the capacity of agroecosystems to maintain food security. The aim of this work was to investigate the impact of environmental conditions generated by photovoltaic (PV) panels for sustaining open-field tomato (Solanum lycopersicum L.) fruit production under varying water supply regimes. Tomato plants were grown beneath PV panels or in full sunlight. In each scenario, two plots with an equal number of plants were subjected to different irrigation levels: high watering (HW) and low watering (LW). The results showed a lower number of tomato fruit produced grown under the PV panels, with an increased fruit size and water content under a normal water supply. The Brix degrees of the tomato fruits grown under the panel were more comparable to the fruits commercially available on the market than the Brix degree of the fruits grown in open-field sunlight. Thus, our data supported the conclusion that the agrivoltaic system, in the context of climate change with the enduring drought and long-term water scarcity, can be a good adaptation strategy to maintain favorable tomato production compared to the full sunlight conditions. Furthermore, these results can be important for planning breeding programs, since in many cases, the tomato fruits grown in full sunlight were seedless.